Ответы и объяснения

2013-02-21T19:31:50+04:00

Выражение: (-1.6-3)*(-1.6+4)-(-1.6+2)*(-1.6+5)

Ответ: -12.4

Решаем по действиям:
1. -1.6-3=-4.6
+1.6
_3_._0_
4.6
2. -1.6+4=2.4
-4.0
_1_._6_
2.4
3. (-4.6)*2.4=-4.6*2.4
4. 4.6*2.4=11.04
X4.6
_ _2_._4_ _
184
_9_2_ _ _
11.04
5. -1.6+2=0.4
-2.0
_1_._6_
0.4
6. -1.6+5=3.4
-5.0
_1_._6_
3.4
7. 0.4*3.4=1.36
X0.4
_3_._4_ _
16
1_2_ _ _
1.36
8. -11.04-1.36=-12.4
+11.04
_ _1_._3_6_
12.40

Решаем по шагам:
1. (-4.6)*(-1.6+4)-(-1.6+2)*(-1.6+5)
1.1. -1.6-3=-4.6
+1.6
_3_._0_
4.6
2. (-4.6)*2.4-(-1.6+2)*(-1.6+5)
2.1. -1.6+4=2.4
-4.0
_1_._6_
2.4
3. -4.6*2.4-(-1.6+2)*(-1.6+5)
3.1. (-4.6)*2.4=-4.6*2.4
4. -11.04-(-1.6+2)*(-1.6+5)
4.1. 4.6*2.4=11.04
X4.6
_ _2_._4_ _
184
_9_2_ _ _
11.04
5. -11.04-0.4*(-1.6+5)
5.1. -1.6+2=0.4
-2.0
_1_._6_
0.4
6. -11.04-0.4*3.4
6.1. -1.6+5=3.4
-5.0
_1_._6_
3.4
7. -11.04-1.36
7.1. 0.4*3.4=1.36
X0.4
_3_._4_ _
16
1_2_ _ _
1.36
8. -12.4
8.1. -11.04-1.36=-12.4
+11.04
_ _1_._3_6_
12.40